If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7(x + 3) = -36 Reorder the terms: 7(3 + x) = -36 (3 * 7 + x * 7) = -36 (21 + 7x) = -36 Solving 21 + 7x = -36 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-21' to each side of the equation. 21 + -21 + 7x = -36 + -21 Combine like terms: 21 + -21 = 0 0 + 7x = -36 + -21 7x = -36 + -21 Combine like terms: -36 + -21 = -57 7x = -57 Divide each side by '7'. x = -8.142857143 Simplifying x = -8.142857143
| 4n+1+1=-18 | | -2(a-9)=108+7a | | 2/3x-5/9×=2 | | 5.7p-18=6.7p-9 | | 18d-18d+4d=20 | | -5-6n=-3n | | -3+x+2x=6 | | x-2.7=5.14 | | -(x+5)=5x-1 | | 3/2x-5/9×=2 | | 25x^2-y/9x^2z-4z÷5x-y/3xz-2z= | | 2x=x-13 | | 2y+-7y-15y+9y=11 | | 72+x+x=(x+1)(x+1) | | 15(v+1)-3v=3(4v+3)-14 | | h-10=2-h | | 9-M=15 | | 2+7=3x+4 | | x-2.7=5.15 | | 19c-10c=9 | | 18=2+2k | | 5x-38=4x-26 | | 8p-7p=20 | | P-61/9=-17/2 | | 9-25x^2+50x+25= | | 6=2/3×-6 | | 12m=11m | | -3x-2(-2+3x)=13 | | 4(x+7)=9x+8 | | -10+7-7y=-5y+9 | | 2x+8+x+9= | | -8(-3-6x)=6(4+2x)-2x |